The historical development of Customary law in traditional societies (Journal of history, 2020)
The article discusses the unity of heritage and historical origins of the customary law of the traditional society. The features of trends conversion of customary law into national legislation. When a scientific analysis of the history of the customary law of the traditional society it must be read in conjunction with the history of the state. Along with this, the author expresses an opinion on the application of the basic legal ideas of customary law for the development of spiritual and moral values of the peoples on the Eurasian space. Key words: traditional, meritocracy, hierarchy, customary law.